Relationship between Skills of Study, Positive Psychological Strengths and Examination Anxiety between Students at the Government Own Education Colleges in Nigeria - et. al., Mustapha Alhaji Grema, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Examination plays a vital role in every contemporary educational set up, as well as being used as a measure to place students in their appropriate position after being examined. Nonetheless a phenomenon associated with the low academic outcomes is a number of students' experiences of examination anxiety that leads to a lack of focus on taking the right examination decision. The aim of this study was therefore to determine the level of study abilities, positive psychological strengths, examination anxiety and the relationship between the variables used in the study with a population of 315 students and 315 students. A positive significant relationship was shown by the relationship of the path model between study abilities and examination anxiety. Also the structural analysis shows that there was a strong relationship between positive psychological strengths and examination anxiety. The Structural Analysis of Research Skills has been very successful and shows a positive coefficient. Positive psychological strengths, with a positive path coefficient, showed a high level of influence on examination anxiety. The study results show that study skills were effective and improved their level of study skills in managing the anxiety of the examination.